2012
DOI: 10.2135/cropsci2011.07.0389
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Spread and Dry Matter Partitioning of Creeping Bentgrass Cultivars

Abstract: Creeping bentgrass (Agrostis stolonifera L.) cultivars are available that possess varying vegetative characteristics. A better understanding of the vegetative growth among creeping bentgrass cultivars is essential to its culture and would aid breeders in selecting for improved turf characteristics in germplasm screening programs. Our objectives were to identify differences in establishment rates among cultivars of creeping bentgrass and to determine the factors associated with differing growth rates by using g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…(Magni et al 2014), Zoysia spp. (Patton et al 2007), and creeping bentgrass (Jones and Christians 2012).…”
mentioning
confidence: 99%
“…(Magni et al 2014), Zoysia spp. (Patton et al 2007), and creeping bentgrass (Jones and Christians 2012).…”
mentioning
confidence: 99%
“…Belesky and Fedders (1995a) conducted a comparative growth analysis of cool‐ and warm‐season grasses, and found that RGR declined when 50% of the canopy was harvested (greater stubble mass), compared with a 75% harvest (less stubble mass). Jones and Christians (2012), reported no differences in RGR between slow‐and fast‐spreading bentgrass ( Agrostis stolonifera L.) cultivars, even though there was a difference of 63% in CGR. Conversely, in the present study there was no difference in CGR during the warm season, but Jiggs had greater RGR due to its lesser initial stubble mass.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, understanding the growth of forage plants is important to optimize management decisions. The growth of a plant can be defined as the increase in size, volume, and mass of one or more organs over time (Hunt, 1990), and it can be quantified by destructive methods involving harvesting the biomass of the plant or canopy, or by nondestructive methods, such as determining the increase in height and volume, and estimating the leaf area index nondestructively.…”
mentioning
confidence: 99%
“…The CGR has limited use in growth analysis because it considers only the variation in herbage mass over time, without taking into account the initial canopy characteristics that affect plant growth, such as leaf area and herbage mass (Cairo et al, 2008). Jones and Christians (2012) compared the growth of two creeping bentgrass ( Agrostis stolonifera L.) cultivars, Bengal and Penncross. They reported that CGR of Penncross was 63% higher than that of Bengal, but when it was corrected for the initial crop characteristics by calculating the RGR, the two cultivars had similar growth rates.…”
Section: Resultsmentioning
confidence: 99%